2016
DOI: 10.1016/j.ahj.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe lesion calcification on clinical outcome of patients with stable angina, treated with newer generation permanent polymer-coated drug-eluting stents

Abstract: In patients with stable angina, severe target lesion calcification is associated with an increased risk of adverse cardiovascular events following treatment with newer generation permanent polymer-coated DES. This increase in risk is restricted to the first year of follow-up, which is an encouraging finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
4
27
1
Order By: Relevance
“…Patients with diabetes mellitus, acute myocardial infarction, and a prior history of coronary artery bypass surgery represent a high-risk population and they are therefore predisposed to an increased incidence of adverse events. Similar to previous reports, we found that moderate/ severe calcification and ostial lesions increased the risk of TLF [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Patients with diabetes mellitus, acute myocardial infarction, and a prior history of coronary artery bypass surgery represent a high-risk population and they are therefore predisposed to an increased incidence of adverse events. Similar to previous reports, we found that moderate/ severe calcification and ostial lesions increased the risk of TLF [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it is plausible that the adverse prognosis attributable to severely calcified lesions may be attenuated with widespread use of newer generation DES. However, existing studies evaluating such associations were limited by modest sample size, inclusion of specific clinical syndromes, or randomized trial participants, thereby limiting generalizability to usual clinical practice. Accordingly, we sought to examine the impact of coronary calcium severity on post‐PCI risk in a contemporary and diverse cohort presenting with stable and acute syndromes treated with newer generation DES.…”
Section: Introductionmentioning
confidence: 99%
“…While CAC occurs in various forms and morphologies, the dense intimal atherosclerotic CAC seen in advanced plaques because of inflammation and repeated periods of disruption and healing creates a technical challenge during PCI. The presence of severe CAC is associated with higher rates of major adverse cardiac events (MACE), including death, myocardial infarction (MI), target vessel revascularization (TVR), and stent thrombosis .…”
Section: Introductionmentioning
confidence: 99%